Neonatal mortality and risk factors in the University Hospital of the Mother and Child Lagoon in Cotonou, Benin, 2015-2016 - Mathilde Houssou; Yolaine Glèlè Ahanhanzo Hessou; Bernard Sawadogo; Simon Antara; André Mckenzie; Mamadou Sawadogo; Laurent Ouedraogo (Journal of Interventional Epidemiology and Public Health)
Introduction: The neonatal period is one of the most vulnerable periods for a child’s survival because of the various attacks and infections, majority of which are avoidable mainly through preventive measures. We assessed neonatal hospital mortality and associated factors in a specialized hospital neonatal center.